Assessment of the Microbial and Physico-Chemical Composition of Tigernut Subjected to Different Fermentation Methods - Bukola, Agbaje Rachael; Olusegun, Oyetayo Victor; Okhonloye, Ojokoh Anthony (Pakistan Journal of Nutrition, 2015)
This research investigate the microbial, physical and proximate composition of tiger nut subjected to different fermentation methods such as traditional, back slope and control. Cleaned tiger nut were fermented for the period of four days in which samples were taken daily from each of the fermented groups to determine the total viable count of microorganisms associated with raw and fermented tiger nut samples, the pH and total titratable acidity. The result of total viable count reveal that back slope fermented milled sample has the highest microbial count of 4.16x105 cfu/g while control fermented sample show the least value (2.30x105 cfu/g). All the fermented samples show increment in lactic acid bacterial count throughout fermentation period. Traditional fermented whole sample had the highest fungal count of 4.40x105 sfu/g while control fermented sample showed the least value (9.33x104 sfu/g). The overall microorganisms isolated and identified from raw and fermented tiger nut were Streptococcus lactis, Lactobacillus plantarum, Staphylococcus aureus, Bacillus subtilis, Micrococcus luteus, Bacillus cereus, Aspergillus niger, Aspergillus fumigatus, Aspergillus flavus and Penicillum italicum. There was significant decrease in pH value while total titratable acidity (TTA) increased in the fermented samples. Fermented whole sample had the highest protein value of 7.65% while raw sample had the least (4.2%) back slope fermented sample had the lowest moisture content (3.5%). There was no significant difference in the value of fat in all the samples. Back slope fermented sample had the highest value in ash (2.5%) and carbohydrate (65.0%) while the least value was recorded in the control fermented sample ash (0.5%) and carbohydrate (45.0%). Traditional and back slope fermentation was the best methods that may increase the proximate composition of tiger nut.